2022
DOI: 10.1021/acsomega.2c02600
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptides with Sialyl Lewis Antigen in Serum Haptoglobin as Candidate Biomarkers for Nonalcoholic Steatohepatitis Hepatocellular Carcinoma Using a Higher-Energy Collision-Induced Dissociation Parallel Reaction Monitoring-Mass Spectrometry Method

Abstract: Nonalcoholic steatohepatitis (NASH) is the fastest growing cause of hepatocellular carcinoma (HCC) in the United States. Changes in N -glycosylation on specific glycosites of serum proteins have been investigated as potential markers for the early detection of NASH-related HCC. Herein, we report a glycopeptide with a Sialyl Lewis structure derived from serum haptoglobin (Hp) as a potential marker for NASH related HCCs among 95 patients with NASH, including 46 cirrhosis, 32 early-stage HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Additionally, the fucosylated Hp/Hp ratio (concentration of fucosylated Hp/concentration of total Hp) and the ELISA index (OD value of fucosylated Hp/OD value of total Hp) were significantly increased in HCC patients compared to (healthy) controls 36,37 . Whereas seven of these studies examined the aberrations in N‐glycosylation status of the Hp protein, 33,34,36,38–41 five studies focused on site‐specific N‐glycosylation patterns of the Hp‐β subunit 35,37,42–44 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the fucosylated Hp/Hp ratio (concentration of fucosylated Hp/concentration of total Hp) and the ELISA index (OD value of fucosylated Hp/OD value of total Hp) were significantly increased in HCC patients compared to (healthy) controls 36,37 . Whereas seven of these studies examined the aberrations in N‐glycosylation status of the Hp protein, 33,34,36,38–41 five studies focused on site‐specific N‐glycosylation patterns of the Hp‐β subunit 35,37,42–44 …”
Section: Resultsmentioning
confidence: 99%
“…As such, a 2‐marker panel (AFP + N241_A4G4F2S4) was developed to discriminate HCC from cirrhosis with an AUC of 0.90. In addition to AFP, this panel represented the bifucosylated tetra‐antennary glycopeptide at site N241 of Hp 42 . Notably, the bifucosylated tetra‐antennary glycan, with both core‐ and antennary‐ fucosylation, was increased in HCC compared to cirrhosis of all aetiologies (HBV‐, HCV‐, and alcohol‐related) 38,39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it is unknown whether the MRM-MS panel is useful for patients with other risk factors for HCC, such as alcoholic liver cirrhosis, or nonalcoholic fatty liver disease. Because the main etiological cause of HCC is shifting from CHB or CHC to NASH or ALD due to vaccination and antivirals, further validation in the ALD and NASH populations is required. , Also, the effectiveness of the MRM-MS panel in patients of various ethnicities is unverifiedall of our participants were Korean. Finally, no comparison with abdominal ultrasonography was performed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Hp is known to have four N-glycosylation sites with various types of sugar chains and mostly sialylation modifications [ 142 ]. It has been reported that the N-glycan type of Hp is altered in patients with liver cancer compared with normal adults [ 143 ].…”
Section: Introductionmentioning
confidence: 99%